Pengertian dan langkah menyusun capaian pembelajaran (CP), alur tujuan pembelajaran (ATP), tujuan pembelajaran (TP), dan modul ajar (MA). - Olivia, Salsabila Dhea (Maliki Interdisciplinary Journal, 2026)
Learning outcomes (CP) are educational goals that students must know, understand, and be able to achieve. Learning Objective Flow (ATP) is a strategy used to design and manage the learning process so that learning objectives can be achieved. Learning Objectives (TP) explain everything students will achieve in the learning process. The learning materials that have been prepared, starting from the opening, core, and closing activities in the learning process, are called learning modules (MA). Learning modules (MA) are created as a reference for teachers and students in the learning process. By improving teacher capacity, optimizing diagnostic, formative, and summative assessments, developing contextual teaching modules to ensure the material is truly relevant and relevant to student characteristics and their school environment, and by collaborating and reflecting on it, allowing teachers to exchange ideas with their colleagues. These suggestions can help us find solutions to improve education and the learning process in Indonesia.